Czech Startup Ecosystem in the Context of the World Successful Startup Ecosystems - Ryplová, Daniela (2025)
This master's thesis examines the Czech startup ecosystem in the context of successsful startup ecosystems in Europe. The main goal of the thesis is to identify key characteristics of advanced startup ecosystems and compare them with the Czech ecosystem in order to assess its position in supporting state innovation. The first chapter defines the concepts of startup and startup ecosystem, explains their economic benefits, and describes metrics used to evaluate startup ecosystem success according to the Global Startup Ecosystem Report 2024 by Startup Genome (GSER). The second chapter analyzes the characteristics of three advanced startup ecosystems – Munich, Stockholm, and Estonia – based on eight standards of the European Startup Nations Alliance (ESNA) and compares them with the Czech ecosystem. The final chapter presents the results of qualitative research conducted through ten semi-structured interviews with Czech startup founders, identifies the main challenges of the Czech startup environment, and proposes possible solutions based on best practices from the analyzed foreign ecosystems.